2019
DOI: 10.1080/09585192.2019.1674360
|View full text |Cite
|
Sign up to set email alerts
|

Employee perceptions of HR practices: A critical review and future directions

Abstract: Scholars are directing more attention to employee perceptions of human resources (HR) practices and have explored issues such as whether and how employees' idiosyncratic or collective perceptions of HR practices shape employee outcomes. To further this area of research, we seek to determine what authors mean when they refer to "employee perceptions of HR practices". We review 105 articles from leading human resource management journals and find that employee perceptions of HR practices is not a monolithic conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
232
0
11

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 152 publications
(251 citation statements)
references
References 206 publications
8
232
0
11
Order By: Relevance
“…We extend prior recent reviews on the employee perspective of HRM (Beijer et al, 2019;Wang et al, 2020). Beijer et al (2019) offered an in-depth review on the conceptualization of employee perceptions of HR practices.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…We extend prior recent reviews on the employee perspective of HRM (Beijer et al, 2019;Wang et al, 2020). Beijer et al (2019) offered an in-depth review on the conceptualization of employee perceptions of HR practices.…”
Section: Introductionmentioning
confidence: 96%
“…40% of the studies in the last four years included employee perceptions of HR practices when studying the relationship between HRM and performance (Beijer et al, 2019). This has resulted in a wide range of conceptual models in which employee perceptions of HR practices have been researched (Wang et al, 2020). These studies have shown that it is employees' perception of HR practices that influences employee behavior, rather than manager-rated implemented HR practices, demonstrating the importance of investigating the employee perspective on HR practices (Den Hartog et al, 2013;Jensen et al, 2013;Kehoe & Wright, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, in search of better understanding employees' perceptions of HRM and how these perceptions are developed, scholars have called for more qualitative research related to this topic (Hewett et al, 2018;Wang et al, 2020), rather than "uncritically borrow(ing) measurements items developed in different empirical contexts" (Wang et al, 2020, p. 155). Our multilevel qualitative approach allowed us to get a better understanding of the support supervisors provide to each employee and employees' interpretations thereof, which would not have been possible when uniform operationalizations of supervisor support were used, as is done in quantitative research methods.…”
Section: Conclusion and Discussionmentioning
confidence: 99%